New constraints on the formation of the helium lines - Houdebine, E; Smith, G; Jordan, C (2003)
We analyse observations of the helium lines obtained with CDS onboard SOHO. The He I 584.3 Angstrom/O III intensity ratio shows a lower limit and an upper limit that decrease with increasing 0 in intensity. At low O III intensities this ratio increases significantly. An upper limit arises naturally if the enhancement mechanism involves turbulent motions transporting the helium atoms and ions through the steep transition region temperature gradient. The He I 537.0-Angstrom/He I 584.3-Angstrom and He II 303.8-Angstrom/He I 584.3-Angstrom intensity ratios both decrease as the He I 584.3-Angstrom line intensity increases. The values of the line ratios support the enhancement of the helium lines by turbulent motions, but appear to rule out the enhancement due to excitation by non-thermal coronal electrons.